On ensuring joint tightness on the basis of technological induction - G. A. Pilyushina; P. G. Pyrikov; E. A. Pamfilov; V. V. Kapustin (Advanced Engineering Research)
Introduction. Some theoretical and engineering aspects of sealing joints through magnetostriction, as well as the polarization of the sealed medium under the external induction are considered. Control of surface roughness of joined parts to increase the joint density when induced by an external magnetic field is studied. The creation of electromagnetic barriers for the migration of molecules of the sealed medium through a sealer is considered. The work objective is to validate the technological conditions for sealing movable joints in the cases described above.Materials and Methods. The conditions for ensuring the joint density are shown as a result of the contact problem solution and as a factor determined by the molecular-mechanical friction theory. Geometric, operational and tribological conditions of joint tightness are accepted. Damping properties of the fixed friction contact are determined by the molecular component. The theoretical and calculated analysis of the factors affecting the joint density is presented. Decrease in the smoothing depth, reduction of the ratio of transverse and longitudinal roughness steps, and increase in the contact area are indicated as the target results of the process preparation of the surfaces of the joint parts. Loss of tightness is defined as a specific transfer of molecules. They are transferred to the area of the joined surfaces or migrate freely through the sealer at the stages of sorption, diffusion and desorption. The predominance of any stage occurs when the entropy changes, and it is due to temperature and pressure. The schemes of sealing joints in the controlled magnetic field and of the dependence of magnetostriction and magnetostrictive stresses on the magnetic field strength are visualized.Research Results. The stability of sealers in highly volatile and gaseous media during their polarization and magnetization in an external field is experimentally investigated. In the former case, the magnetic induction vector was first oriented perpendicular to the longitudinal axis of the joint. A drop in the magnitude of the magnetic flux was observed when the compound was under the on-load operation for 268 hours. The total operating time of the joint was 1070 hours. If the magnetic induction vector was oriented longitudinally to the shaft axis, the operating time to the correction of the field strength was 87 hours. In the gas environment, the operating time of the connection to the adjustment of the tension was 187 hours with a total operating time of 935 hours.Discussion and Conclusions. The penetrating ability of pressurized media decreases in the “gas - vapor - liquid” series. It depends on the temperature at the joint contact. Depressurization can be traced through changes in the magnetic flux determined by the intrinsic magnetic permeability of the molecules of the sealed medium as they penetrate the interface surface.To increase tightness, it is required to suppress the activity of molecules. For this purpose, ionization and induction in the constant and alternating magnetic field with the intensity of <60 kA/m are used.